Ризик: сутність поняття та класифікація в туристичній індустрії - Ярмола, К. М.; Чухрай, Н. І.; Yarmola, K. M.; Chukhray, N. I. (Видавництво Львівської політехніки, 2023)
У статті проаналізовано підходи до розуміння поняття “ризик” та їх трактування у різних сферах діяльності. Особливу увагу приділено вивченню ризиків у галузі туризму. Також розглянуто відмінність між туристичними ризиками та ризиками туристичної індустрії. Систематизовано основні ризики, які впливають на туристичну активність у світі, поділено та погруповано їх на категорії, визначено географію поширення. Також наведено коротку характеристику кожної з виділених груп ризиків та ключові події, які до них відносяться.

Nowadays one of the characteristic features of society‘s functioning is high uncertainty. This is manifested in the impossibility of predicting future events, which creates fear and apprehension to perform some activity in order to protect oneself from undesirable consequences. Uncertainty is the prerequisite for the risks emergence. The purpose of the study is to define the essence of "risk" concept, its classification and systematization, which will allow a better understanding which factors affect tourism activity in the world for the further risk management programs formation. Despite the large number of studies, the authors mostly consider the risks of the tourism industry which affect a separate tourist enterprise activities. The decisive factor for risk management at the micro (enterprise) level is the ability to respond quickly and flexibly, the presence of risk management programs and measures to eliminate consequences. Each group of risks has a different effect on a separate industry or enterprise, and mostly they have a negative character. The tourism industry suffers significantly from conditions caused by natural, climatic, economic, political, foreign economic and other factors. The most devastating event in recent years that caused a significant drop in tourism industry was the COVID-19 pandemic, with an average of 70 % drop in international tourist arrivals for 2020–2022. Due to the existing risks, the tourism industry bears significant financial losses, bankruptcies or structural changes. Different risks require appropriate solutions and support measures. To carry out the research, general scientific and special methods were used, in particular theoretical generalization – to highlight the theoretical aspects of risks in tourism; synthesis, comparison and systematization; statistical analysis method – for analyzing statistical data of tourist flows. The information base is scientific publications of Ukrainian and foreign scientists, as well as data from the World Tourism Organization (WTO). The conducted study of the tourism industry and the risks impact on it gives reason to conclude that it is very sensitive to the risks that arise in society, even one adverse event can leave a negative impression on the destination or the tourist attraction of the country. The results of this research can be useful to develop practical recommendations for risk management at the level of enterprises and the industry as a whole. The article proposes a classification of risks in tourism with information about countries that are most vulnerable to such phenomena as natural disasters, terrorism, environmental and political dangers, etc., thanks to which it is possible to assess the safety of individual destinations. Examples of the various factors influence on the tourism industry of the countries and regions are also given.
Risk: the essence of the concept and classification in the tourism industry
Keywords: ризик; туристичний ризик; ризики в туристичній індустрії; risk; tourist risk; risks in the tourism industry; 338.48-1; 005.334